KETEGUHAN IMAN DALAM PENDERITAAN: INTEGRASI AJARAN PAULUS DAN FALSAFAH SABAR NERIMO JAWA - Pamarto, Ageng Asih (RERUM: Journal of Biblical Practice, 2025)
This study aims to analyze the integration of Apostle Paul's teachings on steadfast faith in suffering and the sabar nerimo philosophy in Javanese culture. A qualitative descriptive method with a literature-based approach was applied, combining the analysis of biblical texts (Romans 5:3–5; Philippians 4:11–13) and Javanese manuscripts (Serat Wedhatama). The results indicate that both Paul’s teachings and Javanese philosophy view suffering as a means of character formation and spiritual development. Paul emphasizes suffering as a path to hope in Christ, while Javanese culture promotes patience and acceptance (nrimo ing pandum) as a form of practical wisdom. Together, these perspectives complement each other in building spiritual resilience and effective coping mechanisms. This article makes an original contribution to interdisciplinary studies in theology and culture, particularly in contextual theology and spiritual psychology, by bridging the teachings of Paul and the Javanese sabar nerimo philosophy, which has been rarely explored. The study is conceptual and literature-based, and has not yet been empirically tested. Future research is recommended to conduct empirical studies with Javanese Christian communities to explore the practical application of Paul’s teachings and sabar nerimo in daily life, thereby enhancing both conceptual validity and real-world relevance.   Penelitian ini bertujuan untuk menganalisis integrasi antara ajaran Rasul Paulus tentang keteguhan iman dalam penderitaan dan konsep sabar nerimo dalam budaya Jawa. Penelitian ini menerapkan metode deskriptif kualitatif dengan pendekatan berbasis studi literatur, menggabungkan analisis teks Alkitab (Roma 5:3-5, Filipi 4:11-13) dan naskah Jawa (Serat Wedhatama). Hasil penelitian menunjukkan bahwa baik Paulus maupun filosofi Jawa memandang penderitaan sebagai sarana pembentukan karakter dan spiritualitas. Paulus menekankan penderitaan sebagai jalan menuju pengharapan dalam Kristus, sementara budaya Jawa mengajarkan kesabaran dan penerimaan (nrimo ing pandum) sebagai bentuk kebijaksanaan hidup. Kedua perspektif ini saling melengkapi dalam membangun ketahanan spiritual dan mekanisme koping yang efektif. Artikel ini memberikan kontribusi orisinal dalam kajian lintas teologi dan budaya, khususnya pada bidang teologi kontekstual dan psikologi spiritual, dengan mempertemukan ajaran Paulus dan falsafah Jawa yang sebelumnya belum banyak diteliti. Penelitian ini bersifat konseptual dan berbasis kajian pustaka, sehingga belum diuji secara empiris. Untuk penelitian lanjutan, disarankan studi empiris dengan responden masyarakat Jawa Kristen untuk mengeksplorasi penerapan ajaran Paulus dan sabar nerimo dalam praktik kehidupan sehari-hari, sehingga validitas dan relevansi konseptual dapat diperkuat.